The Role Of Managerial Principles And Teaching Supervision In Improving Teacher Performance At The Islamic Education Center For Kids - Muhammad Abduh Tuasikal; Lantip Diat Prasojo; Muhyadi Muhyadi (Al-Makki Publisher, 2024)
The Islamic Educational Center for Kids (IECFK) is an important institution that teaches children about Islam and Al-Qur'an. However, many IECFKs need more competent teachers. Therefore, more research is needed to identify ways to improve teacher performance in IECFKs. This study aims to improve the teaching performance of IECFK teachers by enhancing their managerial principles and teaching supervision. Cluster random sampling was used to gather data and electronic questionnaires were sent to 288 IECFK administrators out of 995 IECFKs in Gunungkidul, Yogyakarta. The questionnaires were filled out to collect research data, which was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study found that both managerial principles and teaching supervision positively and significantly impacted teacher performance. These findings can be used to improve the quality of teacher performance at IECFKs and provide recommendations for improvement. Supervision should focus on continuous teacher development. Future research could explore other variables that affect teacher performance, such as school culture, teacher training, and improving teacher welfare.